Survival and risk analysis of 10 months surveillance in elite para athletes - Busch, A.; Kubosch, E. J.; Meidl, V.; Bretthauer, B.; Leonhart, R.; Wrobel, N.; Dallmann, P.; Hirschmüller, A. (British Journal of Sports Medicine, 2021)
Background Injury and illness surveillance in Paralympic athletes was implemented in the past. First studies reported high incidences but are often limited to rates per exposure.